O teor testemunhal no conto "Helga", de Lygia Fagundes Telles: um estudo de memória e identidade - LIMA, Kamila Rodrigues (Universidade Federal do Pará, 2021)
The post-war Brazilian literature is marked by texts whose background a violent scenario, due to the accumulation of disasters collected in the twentieth century. In this paper we analyze the witness content in the tale Helga, by Lygia Fagundes Telles, as well as elucidate the categories memory and forgetting function as narrative strategies in the fabric of texts that have Shoah marks in Brazilian literature.